Cases of occupational dermatitis and asthma in beauticians that were reported to The Health and Occupation Research (THOR) network from 1996 to 2011. (1st July 2014) - Kwok, C.; Money, A.; Carder, M.; Turner, S.; Agius, R.; Orton, D.; Wilkinson, M.
Summary: Background: Beauticians are exposed to many potential allergens in their occupation. Aim: To identify the sources of occupational skin and respiratory disease reported in beauticians, with an emphasis on acrylate chemicals, and to investigate the trends over time. Methods: We used the Health and Occupation Research (THOR) database to identify occupational disease in beauticians between 1996 and 2011. Trend analysis was carried out to look for any change in the allergens reported over this period. Results: In total, 257 cases of contact dermatitis (CD) in beauticians were identified, which were associated with 502 suspected agents. The most frequently cited source of allergic CD was acrylate chemicals. The trend analysis showed a small average annual percentage increase in work‐related CD in beauticians for all agents (1.1%; 95% CI −2.5 to 4.9). There was a small decrease in cases in which acrylates were not cited (−1.7%; 95% CI −5.9 to 2.7), and a statistically significant increase when acrylates were cited (7.4%; 95% CI 0.9 to 14.4). There were 11 cases of occupational asthma. Conclusion: We found an increase in cases of occupational dermatitis associated with acrylates in beauticians over a 15‐year period, and describe other causes of occupational dermatitis.